Clima e vulnerabilidade socioespacial: uma avaliação dos fatores de risco na população urbana do município de São Luís (MA) - Araújo, Ronaldo Rodrigues [UNESP] (2014)
The objective of this thesis was to analyze how climate, associated with the types of building materials these areas of socio-spatial vulnerability, compromises the health of the urban population in São Luís (MA). In particular, the work relates the study of urban climate and thermal comfort to the population's socio-spatial conditions, interdiscipliary, and to the use of the Thermodynamic Subsystem for analysis of the urban climate proposed by Monteiro (1976) as a theoretical and methodological foundation. Monitoring and evaluation of thermal comfort were conducted in indoor environment of nine (9) residential buildings with different patterns, especially socio-spatial vulnerability in São Luis, using mini-digital stations for temperature and relative humidity with sampling frequency of 1 hour during the period from October to November 2012. The comparison between the indoor environment and the outside one was made from data obtained from the meteorological station INMET. The characterization of the socio-spatial vulnerability of the urban area surveyed used as a parameter the intraurban social indicators released in the IBGE census in 2010.In order to classify the thermal comfort factor in residences, the reference rates set by Thom and Bosen (1959) were used. In addition, to evaluate in terms of quality, the level of perception of the patients' thermal comfort and the possible association with certain types of symptoms and diseases, it was applied 40 questionnaires in each of the three monitored areas (Vila Cruzado, Salinas do Sacavém and Forquilha) in order to investigate in theses places if there was any relation between the prevalence of these symptoms with the circulatory diseases due to residential building attributes...